The Relationship between Maternal Anemia Status and Childhood Stunting at Baumata Primary Health Care Center - Maria Aurelia Vianey; Sherly Dewu; Meylani Fernanda Bessie; Imanuddin Imanuddin; Kasmawati Kasmawati; Astati Astati (Laboratory Journal of Infectious Diseases, 2025)
Anemia remains a major public health problem in Indonesia, affecting both mothers and children. Numerous studies have examined the relationship between anemia in mothers and children; however, limited research has specifically focused on the association between maternal anemia status and stunted children during the caregiving period. Mothers who experience anemia during this period are more likely to suffer from fatigue and reduced capacity to meet their children’s basic needs, including breastfeeding, complementary feeding, and maintaining hygiene and nutritional adequacy. Suboptimal caregiving practices may increase the risk of anemia in children, particularly among those who are already stunted. This study aimed to determine the relationship between maternal anemia status and anemia among stunted children. A laboratory-based analytical study with a cross-sectional design was conducted involving 20 pairs of mothers and stunted children selected through purposive sampling. Hemoglobin levels were measured using the cyanmethemoglobin method and analyzed using Fisher’s Exact Test. The results showed that 15% of mothers were anemic, while 65% of stunted children were diagnosed with anemia. However, no significant association was found between maternal anemia status and anemia in stunted children (p > 0,05). In contrast, maternal education level was significantly associated with anemia status in children (p < 0,05). In conclusion, although no statistically significant relationship was observed between maternal anemia and anemia in stunted children, the high prevalence of anemia remains a concern. Various factors may contribute to anemia in mothers and children, including poor dietary intake, chronic infections, limited access to health services, low socioeconomic status, and inappropriate complementary feeding practices. Maternal knowledge emerged as an important factor associated with anemia among stunted children.